The Effects of Beta-Ionone Addition in Perfume on Behavior and Serum Cortisol Level of Stress-Induced Mice - Budiman, Clarissa; Miatmoko, Andang; Tyas, Veronika Earline Pudji Setianing; Ardianto, Chrismawan; Retnowati, Dini (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Stress is a condition that triggers a change in behavior and physiological state, affecting mental health. Beta-Ionone is a monocyclic terpenoid compound that can lower stress levels. However, there is a lack of studies about the anti-stress capability of Beta-Ionone inhalation, although Beta-Ionone is commonly used as a fragrance in perfumes. This study aimed to evaluate the effect of Beta-Ionone addition as the fragrance in perfumes on mice stress. The Beta-Ionone perfume was formulated with Bergamot Oil, Lavender Oil, Eucalyptus Oil, Tea Tree Oil, and Patchouli Oil to produce Fem, Fem-Ion (Fem + Beta-Ionone), Masc, and Masc-Ion (Fem + Beta-Ionone), which had different preferable odors. The anti-stress effectivity was then evaluated in stress induced mice, which were restrained for one hour every day for one week. The perfumes were then given by inhalation every alternate day. The stress level of the mice was evaluated using a tail suspension test and serum cortisol level assays. The results showed that inhalation of the perfumes lowered the immobility time of mice in the tail suspension test, albeit the addition of Beta Ionone did not give a significant difference. Based on the results of serum cortisol level, there was a substantial decrease in serum cortisol by inhaling the Fem and Fem-Ion, showing decreases in stress level. However, there were increases in serum cortisol levels for Masc and Masc-Ion, indicating stress induction, which was suggested to be caused by 1,8-cineole, a compound in the Eucalyptus oil as the perfume oil components.